Unusual Behavior of the Magnetization Reversal in Soft/Hard Multisegmented Nanowires - Altbir-Drullinsky, D; Escrig-Murua, J; Corona-Gonzalez, R (Elsevier B.V., 2017)
The magnetization reversal mechanisms in soft/hard multisegmented nanowires have been investigated using numerical simulations. In most of the studied systems the magnetization reversal process starts at the ends. However in short soft/hard/soft nanowires, the magnetization reversal process starts at the center of the wire, generating an unusual behavior of the coercivity as a function of the length. © 2017 Elsevier B.V.